Red blood cell oxidative stress impairs oxygen delivery and induces red blood cell aging - Mohanty, Joy; Nagababu, Enika; Rifkind, Joseph M. (Frontiers in Physiology, 2014)
Red Blood Cells (RBCs) need to deform and squeeze through narrow capillaries. Thus, decreased deformability of RBCs contributes to the elimination of aged or damaged RBCs from the circulation. This process causes impaired oxygen delivery, which has contributed to the pathology of a number of diseases. Studies from our laboratory have shown that oxidative stress plays a significant role in damaging the RBC membrane and impairing deformability. RBCs are continuously exposed to both endogenous and exogenous sources of reactive oxygen species (ROS) like superoxide and hydrogen peroxide (H2O2). While the bulk of the ROS are neutralized by the RBC antioxidant system consisting of both non-enzymatic and enzymatic antioxidants including catalase, glutathione peroxidase and peroxiredoxin-2, the autoxidation of hemoglobin bound to the membrane is relatively inaccessible to cytosolic antioxidants. This process becomes more pronounced under hypoxic conditions when hemoglobin is partially oxygenated resulting in an increased rate of autoxidation and increased affinity for the RBC membrane. We have shown that a fraction of peroxyredoxin-2 present on the RBC membrane may play a major role in neutralizing these ROS. H2O2 that is not neutralized by the RBC antioxidant system can react with the heme producing fluorescent heme degradation products (HDP). We have used the level of these HDP as a measure of RBC Oxidative Stress. Increased levels of HDP are detected during cellular aging and various diseases. The negative correlation (p< 0.0001) between the level of HDP and RBC deformability establishes a contribution of RBC oxidative stress to cellular stiffness. While decreased deformability contributes to the removal of RBCs from circulation, the uptake of RBCs by macrophages can also involve other processes like caspase-3 activation,which also directly involve oxidative stress. RBC oxidative stress, therefore, plays a significant role in inducing RBC aging.